Design, monitoring and optimisation of distributed energy system - Yang, Ziyi (Nanyang Technological University, 2020)
Distributed energy resources (DERs) have gained prevalence in both industrial applications and academic research projects in recent years. In March 2020, School of EEE purchased EnergyIP Distributed Energy Optimization (DEOP) from Siemens Singapore. This project is to set up the EnergyIP DEOP software platform, as well as the supporting hardware assets, so as to explore various functionalities of EnergyIP DEOP for future research purposes. In this project, the user-friendliness and the flexibility in real-time data visualisation and management were tested. The ability to implement optimisation algorithm using real-time data was also tested with an economic dispatch algorithm. As a result, EnergyIP DEOP is tested to be a versatile and efficient software platform for DERs management in microgrid and it is able to incorporate with designed algorithm to achieve other purposes such as real-time optimisation with the aid of gRPC interface.